EU Fiscal Rules: A Look Back and the Way Forward - Klaus Regling (Intereconomics)
The decline of “natural real interest rates” during the last three decades is a common phenomenon in all advanced economies and can be explained by a number of structural factors: the downward trend in potential growth; population ageing, which has led to higher savings rates in many countries; and the rising inequality in the distribution of wealth, which also increases the average savings rate.